Features of WLAN to build a wireless LAN segment - Мелешко, М. А.; Лазебний, А. В. (Problems of Informatization and Control, 2011)
We consider the design features of wireless LANs (Blyth). Conducted systematization of technical parameters of the hardware cordless networks and the results of experimental investigation of Bani working parametrovm individual components during the test in close to real